The Role of Corporate Social Responsibility, Sales Promotion, and Service Quality Programs on Marketing Performance Mediated by Customer Satisfaction - Tobing, Yehezkiel Lamora Lumban; Shiratina, Aldina (Dinasti International Journal of Digital Business Management, 2024)
This study aims to observe the relationship between CSR programs, sales promotions and service quality on marketing performance mediated by customer satisfaction on Adem Sari Chingku RTD products, which takes a case study in Bogor City. The data analysis method used descriptive and inferential statistics using Partial Least Square (PLS). Analysis used is test of validity, reliability test and coefficient of determination. This study found that CSR has a positive and significant effect on marketing performance, sales promotion has a positive and significant effect on marketing performance, service quality has a positive and significant effect on marketing performance. Customer satisfaction mediates the effect of CSR on marketing performance, customer satisfaction mediates the effect of sales promotion on marketing performance, customer satisfaction mediates the effect of service quality on marketing performance.